Recent Advances in Tannic Acid (Gallotannin) Anticancer Activities and Drug Delivery Systems for Efficacy Improvement; A Comprehensive Review - Rana A. Youness; Rabab Kamel; Nermeen A. Elkasabgy; Ping Shao; Mohamed A. Farag (Molecules, 2021)
Tannic acid is a chief gallo-tannin belonging to the hydrolysable tannins extracted from gall nuts and other plant sources. A myriad of pharmaceutical and biological applications in the medical field has been well recognized to tannic acid. Among these effects, potential anticancer activities against several solid malignancies such as liver, breast, lung, pancreatic, colorectal and ovarian cancers have been reported. Tannic acid was found to play a maestro-role in tuning several oncological signaling pathways including JAK/STAT, RAS/RAF/mTOR, TGF-β1/TGF-β1R axis, VEGF/VEGFR and CXCL12/CXCR4 axes. The combinational beneficial effects of tannic acid with other conventional chemotherapeutic drugs have been clearly demonstrated in literature such as a synergistic anticancer effect and enhancement of the chemo-sensitivity in several resistant cases. Yet, clinical applications of tannic acid have been limited owing to its poor lipid solubility, low bioavailability, off-taste, and short half-life. To overcome such obstacles, novel drug delivery systems have been employed to deliver tannic acid with the aim of improving its applications and/or efficacy against cancer cells. Among these drug delivery systems are several types of organic and metallic nanoparticles. In this review, the authors focus on the molecular mechanisms of tannic acid in tuning several neoplastic diseases as well as novel drug delivery systems that can be used for its clinical applications with an attempt to provide a systemic reference to promote the development of tannic acid as a cheap drug and/or drug delivery system in cancer management.